Rationale and Motivation of Agricultural Producers in Adopting Crop Rotation in the Northern Great Plains, USA. Issue 4 (4th July 2019) - Kasu, Bishal B.; Jacquet, Jeffrey; Junod, Anne; Kumar, Sandeep; Wang, Tong
ABSTRACT: Despite several environmental and economic benefits of crop rotation, the adoption of this agricultural practice is relatively low. Understanding the reasons for low adoption is important from a sustainability policy perspective. This study explores the motivation, challenges, and sources of information of agricultural producers who participate in crop rotation practices in South Dakota, North Dakota, and Nebraska. The findings of a mail survey of 672 producers in these three states show that producers are familiar with the crop rotation practice. Economic profitability is found to drive motivation for crop rotation adoption. The results of a binary logistic regression model show that a producer who perceives that crop rotation is beneficial to farm profitability is 1.83 times more likely to adopt it than the producer who does not believe in its profitability to the farm. The lack of time or resources is the primary barrier to the adoption of crop rotation practice. This study provides additional evidence in support of the importance of farm profitability for the adoption of the practice of crop rotation. Understanding the rationale and addressing the challenges faced by agricultural producers would be useful in planning and policy making of sustainable agriculture.